2006
DOI: 10.1298/jjpta.9.21
|View full text |Cite
|
Sign up to set email alerts
|

EMG Analysis of Lower Extremity Muscles in Three Different Squat Exercises

Abstract: Abstract. The purpose of this study was to come across an exercise that increases the Hamstring contraction levels so that it may protect the anterior cruciate ligament (ACL). Previous studies have postulated that changing the projection of the center of gravity behind the feet will decrease the translation of the tibia, therefore protect the ACL. Muscle activity of the quadriceps, hamstring and soleus muscles in healthy subjects was measured with an EMG during three different squat tasks with differences of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Although unexpected, this may explain why the ankle joint decreased due to increased ankle torque as a sum of all the vertical forces. This main effect was consistent with the result of previous investigations that widening the hip angle decreases the RF muscle activity which functions to flex the hip joint (Nishiwaki et al, 2006;Nordin and Frankel, 2001;Perotto et al, 1994;Yamada and Demura, 2004). In the ankle strategy, TA becomes important to transport the whole body angularly forward with respect to the ankle joint as a center of rotation.…”
Section: Discussionsupporting
confidence: 91%
“…Although unexpected, this may explain why the ankle joint decreased due to increased ankle torque as a sum of all the vertical forces. This main effect was consistent with the result of previous investigations that widening the hip angle decreases the RF muscle activity which functions to flex the hip joint (Nishiwaki et al, 2006;Nordin and Frankel, 2001;Perotto et al, 1994;Yamada and Demura, 2004). In the ankle strategy, TA becomes important to transport the whole body angularly forward with respect to the ankle joint as a center of rotation.…”
Section: Discussionsupporting
confidence: 91%
“…Another data set presented in the work of Nishiwaki et al . [18] is restricted to three exercises of lower limbs performed by nine subjects. The activity of four leg muscles was recorded with EMG (electromyography) electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…U n f o r t u n a t e l y , h o w e v e r , i n -d e p t h investigations of the muscular demands for performing the squat-to-stand (SQ-ST) movement have been few in number. Although the kinematics of sit-to-stand has been investigated 6 ) the contribution of deep flexion of body joints in full squatting to standing has not been subjected to any detailed analysis even though the squatting posture has been addressed in various studies 8) . In the framework of movement cycle analysis, Nuzik et al 6) proposed that the movement of rising to standing basically consists of two phases: forward movement to generate an anterior momentum (flexion phase) and upward movement to extend the body joint and to achieve balance stabilization (extension phase).…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of movement cycle analysis, Nuzik et al 6) proposed that the movement of rising to standing basically consists of two phases: forward movement to generate an anterior momentum (flexion phase) and upward movement to extend the body joint and to achieve balance stabilization (extension phase). Previous studies have reported that rising to standing from a position of 90-degree knee flexion (semi-squat) requires a large amount of quadriceps muscle activity 8) . Although the SQ-ST movement cycle from the semi-squat position to standing has been investigated 8) , the requirements of rising from full knee flexion remain unknown, except for studies which have analyzed the basic movements of human daily activity in the tiptoe posture 5,9,10) , in particular those treating foot position as a determinant factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation